Influence of Economic and Political Factors on the Public Rail Transport - Jiri Cejka; Martin Telecky (Communications - Scientific letters of the University of Zilina, 2019)
The goal of the paper is to assess the territorial development in terms of the public rail transport in conditions of the Czech Republic or, more precisely, in the south of Bohemia. The capacity utilisation of the railway line No. 190 in the direction from Ceske Budejovice to the target station of Strakonice is analysed and the suitable deployment of the set of wagons, intended to be used in providing the basic transport services in the low-populated areas, is evaluated. The paper is concerned with the current situation in utilising the capacities on the railway line No. 190 with respect to the future utilisation of the railway links that will be affected by economic factors in the form of the reduced fare for students and pensioners. To this end, the mathematical and statistical methods, which will pre-define the suitability of the choice of capacities of the set of wagons in providing the basic transport services, will be applied.